INTEGRASI PENDEKATAN STEAM DALAM PEMBELAJARAN SAINS UNTUK MENINGKATKAN KREATIVITAS DAN KOLABORASI SISWA SD - Syarifuddin, Anggun Purnama Sari; Asmelawati, Marlina, Yosmeri Zalfianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning approach has emerged as a significant innovation in addressing the challenges of 21st-century education, particularly in fostering students' creative and collaborative thinking skills. This study aims to examine the integration of the STEAM approach into science learning at the elementary school level and to explore its influence on enhancing students’ creativity and collaboration. The method used is a literature review, analyzing various relevant scholarly sources such as national and international journals, seminar proceedings, and educational policy documents published between 2014 and 2024. Thematic analysis was conducted to explore the fundamental principles of STEAM, its integration strategies, and its impact on the learning process. The findings indicate that implementing STEAM significantly improves students' critical thinking, creativity, and collaboration skills. Several studies reveal that combining STEAM with project-based learning models or contextual experiments creates an active and meaningful learning environment. However, implementing STEAM in Indonesian elementary schools still faces several challenges, including limited teacher understanding, inadequate facilities and infrastructure, and the absence of clear operational guidelines. Therefore, continuous teacher training and supportive education policies are essential for optimal implementation of this approach. This study is expected to contribute to the development of innovative and contextual science learning models aimed at equipping students with comprehensive 21st-century skills.